2015
DOI: 10.5055/jom.2015.0251
|View full text |Cite
|
Sign up to set email alerts
|

Treatment changes following aberrant urine drug test results for patients prescribed chronic opioid therapy

Abstract: Current methods for optimizing treatment after obtaining aberrant UDT results should be enhanced. To improve the utility of UDT to reduce prescription opioid misuse, additional interventions and support for clinicians need to be developed and tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…As for a study conducted by Katz et al (14), 26 (21.3%) of the 122 patients tested were positive for illicit drugs (marijuana 16.4% and cocaine 4.9%). Lastly, Morasco et al (24) found 28.8% of their patients were positive for marijuana and 2.5% were positive for cocaine ( Table 3). The range of positive results for illicit substances could be due to different patient populations (suburban vs. urban) included in the studies as well as differences in medical marijuana laws in various states (24).…”
Section: S141mentioning
confidence: 92%
See 1 more Smart Citation
“…As for a study conducted by Katz et al (14), 26 (21.3%) of the 122 patients tested were positive for illicit drugs (marijuana 16.4% and cocaine 4.9%). Lastly, Morasco et al (24) found 28.8% of their patients were positive for marijuana and 2.5% were positive for cocaine ( Table 3). The range of positive results for illicit substances could be due to different patient populations (suburban vs. urban) included in the studies as well as differences in medical marijuana laws in various states (24).…”
Section: S141mentioning
confidence: 92%
“…Lastly, Morasco et al (24) found 28.8% of their patients were positive for marijuana and 2.5% were positive for cocaine ( Table 3). The range of positive results for illicit substances could be due to different patient populations (suburban vs. urban) included in the studies as well as differences in medical marijuana laws in various states (24). Even though medical marijuana is approved in 23 states, it is still against laws of the federal government to consume it for recreational or non-recreational (i.e., "medical") purposes, and this causes some ambiguity for pain physicians when attempting to treat patients who may be using marijuana for medicinal purposes.…”
Section: S141mentioning
confidence: 92%
“…4,5 Evidence of high-risk behaviors, such as UDTs that are positive for illicit or non-prescribed controlled substances, may lead to discontinuation of long-term opioid therapy (LTOT). 6 Among a national sample of patients who were discontinued from LTOT, 37% were discontinued because of an aberrant UDT. 7 While current recommendations suggest tapering or discontinuing opioid therapy and considering substance use treatment when indicated, 8 data about the care patients receive following LTOT discontinuation are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Cannabis is among the most common substances to be detected on a UDT among chronic pain patients prescribed LTOT. 6,7 More than half of the US and the District of Columbia (DC) have passed legislation to allow medical cannabis use, and eight of these states and DC also allow recreational cannabis use. 8 These trends suggest a growing public acceptance of cannabis, despite limited evidence for effective pain management for most chronic pain conditions.…”
Section: Introductionmentioning
confidence: 99%
“… 10 Even with urine drug test monitoring, providers often fail to respond to abnormal results. 11 These areas of enquiry are all important, but do not address the management of problematic behaviours when they arise. Further, we argue that gaps in knowledge about how to respond to these behaviours are a barrier to optimal implementation of opioid guidelines.…”
Section: Introductionmentioning
confidence: 99%